2022
DOI: 10.3390/nu14071501
|View full text |Cite
|
Sign up to set email alerts
|

Flazin as a Lipid Droplet Regulator against Lipid Disorders

Abstract: Lipid disorders are closely related to numerous metabolic diseases, and lipid droplets (LDs) have been considered as a new target for regulating lipid metabolism. Dietary intervention and nutraceuticals provide safe and long-term beneficial effects for treating metabolic diseases. Flazin is a diet-derived bioactive constituent mainly existing in fermented foods, of which the lipid metabolism improvement function has not been studied. In this study, the effect of flazin on lipid regulation at both cell level an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Flazin was originally isolated as a fluorescent substance from Japanese rice wine lees in 1936, and the structure was determined in 1986. , Flazin was also isolated from tomato juice . Although its biological effects have recently been studied, no studies have examined the inhibition of microbial sporogenesis. Naringenin is a flavanone that is widely distributed in nature, especially in fruits and vegetables, and many biological effects of naringenin have been reported.…”
Section: Resultsmentioning
confidence: 73%
“…Flazin was originally isolated as a fluorescent substance from Japanese rice wine lees in 1936, and the structure was determined in 1986. , Flazin was also isolated from tomato juice . Although its biological effects have recently been studied, no studies have examined the inhibition of microbial sporogenesis. Naringenin is a flavanone that is widely distributed in nature, especially in fruits and vegetables, and many biological effects of naringenin have been reported.…”
Section: Resultsmentioning
confidence: 73%
“…The treatment of FA to cells has profoundly affected the LD TG profile in our previous reports [ 24 , 27 ]. Currently, the results of FA18:1, FA18:2, and FA18:3 that were supplemented to HK-2 cells supported this viewpoint, as they were supposed to be taken up directly by the cells and be esterized as LD TG, while FA16:0, FA20:4, FA20:5, and FA22:6 showed no such function.…”
Section: Resultsmentioning
confidence: 93%
“…The PC/TG ratio exhibited a decreasing trend with the extended oxidation time, reaching 59.6 to 17.9% of the control (0 h) from 0.5 h to 4 h. The PC forms the cylindrical structures in the biological membranes, while the PE form the conical structures [ 38 ]. Therefore, a decreased PC/PE ratio is considered to promote packing defects and thereby favor the localization of perilipin to the LD surface, which contributes to lipid accumulation and LD growth [ 27 ]. According to the present results, the supplemented oxHDL decreased the PC/PE ratio, which suggested that it would aggravate the effect on the packing defects and result in LD enlargement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations